Beyond the Silver Screen: Exploring Future Public Life Through Sociological Film Analysis - Eren, Ibrahim; Aktan, Esin Ozlem Aktuglu (SAGE PUBLICATIONS INC, 2024)
This study seeks to interrogate prospective configurations of public life through science fiction films, particularly by addressing the effects of technological advances and changes on society. In the study's methodology, 27 films were assessed using the sociological film analysis method. In these films, an analysis was conducted on thematic elements, encompassing aspects such as the physical environment, socio-cultural structures, public life, technological infrastructure, and dynamics of human relationships. As a result, a codex of thematic codes was meticulously crafted. The main findings indicate that the films contain scenarios that discuss the boundaries of public space and reflect future social structures. The emphasis appears to be on how and to what extent technology is used. This research presents novel ideas and a platform for discussion for urban planning, architecture, social sciences, and film studies. The originality of this study lies in its analysis of cinematographic content from a sociological standpoint, providing an in-depth perspective on the future of public life and adding a new dimension to the existing body of knowledge on the subject.
Keywords: public life; science fiction movies; sociological film analysis; technological advances; social change; cinematic analyses; future cities; Social Sciences - Other Topics